Nutritional Scenario of Adolescent Boys in Dhaka University Campus (Bangladesh Journal of Nutrition, 2015)
A cross sectional study was carried out among the adolescent boys (11-15 years) in two selective schools (University Laboratory School and Udoyan School) in Dhaka University campus to investigate the nutritional and health status as well as socioeconomic condition. Nutritional status was determined anthropometrically and biochemically (hemoglobin estimation). According to the body mass index, two-third of the boys (75.7%) were normal, 15.4% were over-weight and only 8.9% were found to be thinner. The percent prevalence of anemia was 7.1% based on WHO criteria and the mean hemoglobin level was 14.35 g/dl (±1.38). Energy intake of the boys aged 11-12 years met 79.31% of RDA and those of 13-15 years met 76.09% of RDA. Protein intake of all the boys was more than RDA. Dietary intake of vitamin A was more than 90% of RDA. and that for thiamin and niacin was more than RDA. Iron intake was 60.4% and 66.45% of RDA for the two groups of boys. Vitamin C intake was inadequate (46.76% and 36.06% RDA) for the respective group of boys. Nutritional status (anthropometric) is directly associated with expenditure on food. Percentage of thinness decreased as expenditure on food increased. Monthly expenditure on food had significant relation with hemoglobin level of the adolescents. Most of the participants (67 .5%) did not suffer from any disease. Rest of the boys suffered from fever (23.6%), diarrhea (10.9%), common, cold (29.1 %), respiratory infection (9.1 %), measles (3.6%), typhoid (5.5%) and others (18.2%).5